2014
DOI: 10.1016/j.placenta.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Midregional pro-adrenomedullin plasma concentrations are blunted in severe preeclampsia

Abstract: Levels of the peptide hormone adrenomedullin (AM) are elevated during normal pregnancy, but whether this differs during complications of pregnancy remains unresolved. AM can be quantified by measuring its preprohormone byproduct, midregional pro-adrenomedullin (MR-proADM). MR-pro ADM has shown prognostic value as a biomarker of heart failure, sepsis, and community-acquired pneumonia. Given the relevance of AM to pregnancy, we tested the hypothesis that MR-proADM provides a biomarker for preeclampsia. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Alternatively, fetal renal excretion into the AF might have occurred. Higher MRproADM levels in multiple pregnancies with a relatively larger amount of total placental tissue, as shown in our study (Table 5), and lower levels in placental insufficiency (18) support a placental origin of MRproADM.…”
Section: Discussionsupporting
confidence: 84%
“…Alternatively, fetal renal excretion into the AF might have occurred. Higher MRproADM levels in multiple pregnancies with a relatively larger amount of total placental tissue, as shown in our study (Table 5), and lower levels in placental insufficiency (18) support a placental origin of MRproADM.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, AM signaling is increasingly been recognized as a necessary pathway for vascular remodeling and immune response in physiological states such as pregnancy [23], and disrupted AM signaling is shown to contribute to several pathophysiological states such as preeclampsia [24], systemic and pulmonary hypertension [25, 26], myocardial infarction [27], tumors [28], and lymphedema [29]. Further, Calcrl-RAMP complexes are being explored as important drug targets to treat acute myocardial infarction, pulmonary hypertension, migraine headache, cancer, and several other disorders [3032], indicating that AM signaling axis can be targeted to develop therapies.…”
Section: Resultsmentioning
confidence: 99%
“…92,93 Biomarkers for HFpEF and preeclampsia Two studies on MRproADM described significantly higher levels in pre-eclampsia vs. controls. 95,96 Two studies on c-Tn1 described elevated levels in preeclampsia compared with controls, 97,98 of which only one with statistically significant result. 97 Tumour angiogenesis markers in pre-eclampsia Cancer antigen 125 and carcino-embryonic antigen Three studies reported on CA-125 levels in pre-eclampsia vs. controls, 26,99,100 of which two studies described significantly lower CA-125 levels in PE 99,26 and one did not show significantly different CA-125 levels between pre-eclampsia and controls.…”
Section: Insulin Plasma Glucose and Fatty Acid-binding Proteinmentioning
confidence: 99%